Design of Image Processing Embedded Systems Using Multidimensional Data Flow - Keinert (Springer, 2012)
This book presents a new set of embedded system design techniques called multidimensional data flow, which combine the various benefits offered by existing methodologies such as block-based system design, high-level simulation, system analysis and polyhedral optimization. It describes a novel architecture for efficient and flexible high-speed communication in hardware that can be used both in manual and automatic system design and that offers various design alternatives, balancing achievable throughput with required hardware size. This book demonstrates multidimensional data flow by showing its potential for modeling, analysis, and synthesis of complex image processing applications. These applications are presented in terms of their fundamental properties and resulting design constraints. Coverage includes a discussion of how far the latter can be met better by multidimensional data flow than alternative approaches. Based on these results, the book explains the principles of fine-grained system level analysis and high-speed communication synthesis. Additionally, an extensive review of related techniques is given in order to show their relation to multidimensional data flow.